2010
DOI: 10.1136/ard.2010.141473
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genetic architecture of osteoarthritis from stage 1 of the arcOGEN study

Abstract: ObjectivesThe genetic aetiology of osteoarthritis has not yet been elucidated. To enable a well-powered genome-wide association study (GWAS) for osteoarthritis, the authors have formed the arcOGEN Consortium, a UK-wide collaborative effort aiming to scan genome-wide over 7500 osteoarthritis cases in a two-stage genome-wide association scan. Here the authors report the findings of the stage 1 interim analysis.MethodsThe authors have performed a genome-wide association scan for knee and hip osteoarthritis in 317… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 10 publications
3
75
2
2
Order By: Relevance
“…However, this has not been replicated in other reports, including some 406 recent genome-wide studies (Panoutsopoulou et al, 2011).…”
mentioning
confidence: 42%
See 1 more Smart Citation
“…However, this has not been replicated in other reports, including some 406 recent genome-wide studies (Panoutsopoulou et al, 2011).…”
mentioning
confidence: 42%
“…(Arcogen Consortium, 2012;Panoutsopoulou et al, 2011 been related to osteoporosis in genetic association studies (Ralston,90 2010; Riancho et al, 2011;Richards et al, 2009;Styrkarsdottir et al, 91 2009; Valero et al, 2011 …”
mentioning
confidence: 99%
“…This has given support to the hypothesis of a developmental origin of osteoarthritis [102 104]. The importance of developmental factors is also emphasized by recent results from genome-wide association studies [105,106]. Somewhat unexpectedly, these studies have not revealed significant associations between osteoarthritis and genes typically involved in cartilage homeostasis, such as those encoding proteases.…”
Section: Osteoarthritismentioning
confidence: 84%
“…Another orthopaedic condition, osteoarthritis, has also been intensively investigated by GWASs. Identifying clearly replicated signals has proven challenging, but potential candidate genes that are worthy of further investigation have been identified [45][46][47][48][49][50][51][52][53] . Although we expect that larger ongoing GWASs will replicate the known associations, we expect that such investigations will also identify new genes that yield novel insights into osteoporosis and osteoarthritis.…”
Section: Gwass For Orthopaedic Diseasesmentioning
confidence: 99%